(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The article deals with the semantic transformation of names of food as idiom’s components in Russian phraseology and parоemia discourse. The actuality of the work is determined by anthropocentrism of modern linguistics, interest to interrelation between language and culture, to modelling of national language world views. Specific representatives of the situations are the means of reflection of everyday consciousness in the image-bearing language world view. The images of the dishes are a part of the national world view. The purpose of the work is to describe the specifics of contents and semantic transformation of components – names of food products in Russian phraseological units, including paroemias. Based on 1,000 phraseological contexts of the Russian language, the phraseological “menu” has been created that demonstrates the variety of traditional cuisine: bakery products, drinks, snacks, spices, soups, ritual and holiday dishes, farinaceous, dairy products, desserts. The process involved identification of the most frequent denominations, description of the semantics of the denominations хлеб (“bread”), щи (“shchi”), каша (“porridge”), молоко (“milk”), масло (“butter”), яйцо (“egg”), etc. The motivational signs for the semantic transformation may be taste and contents of the products, their appearance, result of consuming, cooking process, eating process, etc. The components – names of food products, while being within phraseological units, acquire both abstract and concrete meanings: хлеб (“bread”) – ‘home and food’; ‘maintenance’; ‘earnings, payment’; ‘the most necessary’; каша (“porridge”) – ‘mess, disorder’; ‘action, including the one that is hard or unpleasant’; ‘punishment’; ‘life experience’, etc. It has been established that the majority of phraseological units are of Russian-specific origin. Individual phraseological units got into the standard language from jargon speech. Significant number of phraseological units of literary language – both Russian and adopted – have been recorded. It is recognized that the phraseology of Russian language actively masters not only native but also adopted denominations of products. The names of the traditional Russian cuisine are predominantly the ones subjected to semantic transformation. It is the phraseological image that most frequently preserves the national specific of a phraseological unit.